2016
DOI: 10.1016/j.semcdb.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Favorable genomic environments for cis-regulatory evolution: A novel theoretical framework

Abstract: Cis-regulatory changes are arguably the primary evolutionary source of animal morphological diversity. With the recent explosion of genome-wide comparisons of the cis-regulatory content in different animal species is now possible to infer general principles underlying enhancer evolution. However, these studies have also revealed numerous discrepancies and paradoxes, suggesting that the mechanistic causes and modes of cis-regulatory evolution are still not well understood and are probably much more complex than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 112 publications
(140 reference statements)
2
16
0
Order By: Relevance
“…Furthermore, the Msx -CNE ( Msx -CNE-1), 5’ of the coding sequence, and one ZNF503/703 -CNE ( ZNF503/703 -CNE-1) have been experimentally verified by previous studies (Holland et al 2008; Hufton et al 2009; Royo et al 2011; Clarke et al 2012). Finally, for all of these eight cephalochordate-vertebrate CNEs, we found that the sequence conservation between the two cephalochordates ( A. lucayanum and B. floridae ) clearly extends beyond the core CNE regions, echoing the trend previously observed in vertebrates (McEwen et al 2009; Maeso and Tena 2016) that flanking sequences of ancient CNEs tend to be more conserved between more closely related lineages. …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the Msx -CNE ( Msx -CNE-1), 5’ of the coding sequence, and one ZNF503/703 -CNE ( ZNF503/703 -CNE-1) have been experimentally verified by previous studies (Holland et al 2008; Hufton et al 2009; Royo et al 2011; Clarke et al 2012). Finally, for all of these eight cephalochordate-vertebrate CNEs, we found that the sequence conservation between the two cephalochordates ( A. lucayanum and B. floridae ) clearly extends beyond the core CNE regions, echoing the trend previously observed in vertebrates (McEwen et al 2009; Maeso and Tena 2016) that flanking sequences of ancient CNEs tend to be more conserved between more closely related lineages. …”
Section: Resultssupporting
confidence: 81%
“…Similarly, in vertebrates, some CNEs associated with GLI3 , which transduces Shh signaling, show conserved expression in mouse and zebrafish, while one CNE, which directs expression to the limb bud in the mouse and chick, directs expression to the notochord and blood cell precursors, but not to the limb, in the zebrafish (Anwar et al 2015). In fact, such examples of acquiring new regulatory functions by co-option or modification of preexisting CNEs are prevalent in the evolution of new regulatory elements (Maeso and Tena 2016). …”
Section: Discussionmentioning
confidence: 99%
“…De-repression/activation of cryptic (or normally dormant) promoters to drive ectopic expression is one mechanism that can lead to oncogenic effects [3440]. Because TEs, and especially ERV LTRs, are an abundant reservoir of natural promoters in the human genome [6, 41, 42], inappropriate transcriptional activation of typically repressed LTRs may contribute to oncogenesis. Here we review examples of such phenomena, which we term “onco-exaptation”, and propose two explanatory models to understand the role of LTRs in oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…One underappreciated mechanism that can cause gene deregulation in cancer is activation of cryptic (or normally dormant) promoters [14]. Transposable elements (TEs), including endogenous retroviruses (ERVs) and long interspersed elements (LINEs), comprise nearly half of the human genome [57] and represent an abundant source of natural promoters in the genome [8, 9]. In particular, ERV long terminal repeats (LTRs), the termini of integrated retroviruses, naturally harbor promoters and enhancers.…”
Section: Introductionmentioning
confidence: 99%